Abundance of fin (Balaenoptera physalus) and sei whales (B. borealis) amid oil exploration and development off northwest Scotland - Macleod, K.; Simmonds, M. P.; Murray, E. (J. Cetacean Res. Manage., 2023)
A ship-based line transect survey was conducted during July-August 1998 to assess the distribution and abundance of cetaceans off northwest Scotland. Limited information from dedicated surveys exists for this area and the lack of baseline data is cause for concern given the expanding oil industry in these waters. Historical whaling records show that large numbers of baleen whales, particularly fin and sei whales, were captured in these waters during summer. The waters surveyed included former whaling grounds and currently licensed oil blocks to the west of the Outer Hebrides and the Faroe-Shetland Channel and both fin and sei whales were encountered. Neither species was recorded to the west of the Outer Hebrides whereas relatively high densities of both were recorded further north in the Faroe-Shetland Channel. The density of fin and sei whales was 0.021km–2 and 0.022km–2, respectively. Abundance was estimated as 933 (CV=0.38) fin whales, 1,011 (CV=0.35) sei whales and 1,923 (CV=0.33) ‘large whales’. The high density of whales recorded in the Faroe-Shetland Channel supports the idea that it is an important summer feeding ground for both species and the potential for acoustic disturbance associated with increasing industrialisation of this area is a concern. Factors affecting the distribution and abundance of these whales are discussed.